THE EFFECT OF ADHESIVE PAPER WASTE WEIGHT PERCENTAGE IN BIOBRIQUET DERIVED FROM CASSAVA SKIN WASTE - Aneka Firdaus; Aditha Verdinan Panae (Asosiasi Peneliti Sriwijaya, 2020)
Cassava skin waste is waste originating from cassava plants from tapioca flour factories or cassava processed product factories. Indonesia is one of the biggest countries that produces cassava. The number of cassava processing industries in Indonesia is large so that a positive correlation can be drawn that the high amount of cassava processed will produce more cassava skin waste. Based on the results of tests conducted, the higher the composition of the Each cassava can produce 10-15% of cassava skin waste. Cassava skin waste is directly removed, can cause buildup that results in environmental damage. Cassava skin waste is obtained from local farmers, where on average each cassava produces 10-15% of waste. In general, this waste is not used and just thrown away. This research was conducted with the main ingredients of cassava peel waste and adhesive made from used paper. The composition of the mixture of cassava peel and used paper varies, where the percentage by weight of the adhesive starts from 7.0% to 10% with an increase in the composition every 0.5%. Then the biobriquette carbonization process was carried out at a temperature of 400 ° C. The biobriquette characterization was carried out based on ASTM standards to analyze water and ash, volatile matter and heating value. The results of the analysis on the composition of the lowest cassava bark had the highest heating value of 5888 cal / gr with the lowest water, ash and volatile matter content.